Issues and Challenges on Khairat Death Fund Management in Malaysia - Nuur Halimatus Saadiah Masrukhin; Azrul Azlan Iskandar Mirza; Khairil Faizal Khairi; Syadiyah Abdul Shukor (International Journal of Emerging Issues in Islamic Studies, 2022)
Khairat Death Fund, also known as Khairat Kematian, is an organization that plays an important role in the Malay Muslim community in Malaysia. Its main role is to ensure that the death of a Muslim is handled in an appropriate manner. In Malaysia, the Khairat Death Fund is administered by either the qaryah Mosques or the local village associations. Both entities are responsible for administering the fund. Nevertheless, the research and development efforts of Khairat Death Fund have not yet reached the optimal level. Therefore, this paper aims to analyze some of the issues and challenges faced in managing the Khairat Death Fund to ensure that it continues to play an important role as one of the Islamic financial instruments. This study is important because it will help the Khairat Death Fund management organizations and related bodies to take measures that will eventually allow the Khairat Death Fund to be raised and developed as one of Islamic financial instruments. This research adopted a qualitative approach that involved conducting semi-structured interviews with four organizations involved in the management of Khairat Death Fund. The results of this study indicate that Khairat Death Fund organizations are facing with six of issues and challenges which are, low awareness, delay of annual fees payment, differences of costs for muslim funeral, limited investment strategy, cancellation of coverage and uncover group and differences of khairat death fund fees and benefits. It is hoped that this study will contribute to achievement the development of Khairat Death Fund to be more innovative and competitive product in future.